Student funding and student success: A case study of a South African university - Naidoo, A.; McKay, T.J.M. (South African Journal of Higher Education, 2019)
This study sought to establish the relationship between student matriculation results, bursary funding and academic performance. It involved an analysis of 8099 undergraduates for the 2011 cohort year at one particular high education institution in South Africa. This 2011 cohort was tracked over a period of three years. Results show that in terms of student academic performance, Grade 12 National Senior Certificate results are a weak predictor of academic success, whilst grades weighted by module credits were a statistically better predictor of performance and throughput. Thus, enrolment decisions based solely on matriculation results are not recommended. No relationship was found between either the presence, or the value of individual student bursary funding, and throughput. Thus, student academic performance is not a function of bursary funding, although merit bursaries awarded on academic merit yielded the best results. Lastly, there was a statistically significant relationship between being placed in a student residence and academic performance and throughput. That is, students accommodated in official student residences were more likely to graduate within the minimum time than those who were not.